Customer satisfaction towards quality of mail services (Post express, Poslaju and Parcel) in the Pos Malaysia Batu Pahat / Nor Azylia Mohd Alias - Mohd Alias, Nor Azylia (2004)
Post office, Pos Malaysia Batu Pahat is one of Pos Malaysia Berhad district branches in Johor. It has been established in Jalan Rahmat, Batu Pahat since 1932. It has services that been one of the well-known outlets of postal services to the residents of Batu Pahat. This research, which studies the customers' satisfaction, could give some ideas to post office, Pos Malaysia Batu Pahat regarding its external customers management. The aim of this study is to find out how far Pos Malaysia Batu Pahat customers are satisfied with the mail services available that one provided in post office. Several factors are related such as mail services provided, problems that occur when using the Post Express, Poslaju and Parcel services, the staff management in doing the tasks given, efficiency and effectiveness, timeless and others a little influence of quality, productivity performance of the mail services given by the post office. Literature review is conducted to obtain the information and review regarding the quality mail services provided in the post office, Pos Malaysia Batu Pahat. The research paper outlines the interpretation of data and finding analysis, which are based on the questionnaires and interview conducted. Convenience and judgment sampling has been utilized with 60 respondents as the sample size. A self-administered questionnaire was used as the survey instruments beside interviews as the sources of primary data. By using Statistical Package for Social Science-SPSS" (Version 11).(SPSS), results are analysed and beside that, conclusion and recommendations have been made according to the result from the findings. Finally, the researcher also has included the suggestion and comments from the respondents and from the point of view through the observation as a step to improve the mail services in the post office, Pos Malaysia Batu Pahat.